2016
DOI: 10.1161/circheartfailure.115.002314
|View full text |Cite
|
Sign up to set email alerts
|

Choline Diet and Its Gut Microbe–Derived Metabolite, Trimethylamine N-Oxide, Exacerbate Pressure Overload–Induced Heart Failure

Abstract: Background Trimethylamine N-oxide (TMAO), a gut microbe dependent metabolite of dietary choline and other trimethylamine containing nutrients, is both elevated in the circulation of patients suffering from heart failure (HF) and heralds worse overall prognosis. In animal studies, dietary choline or TMAO significantly accelerate atherosclerotic lesion development in ApoE deficient mice, and reduction in TMAO levels inhibits atherosclerosis development in the LDL receptor knockout mouse. Methods and Results C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
244
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(258 citation statements)
references
References 22 publications
6
244
1
7
Order By: Relevance
“…Similar to our observations in angiotensin-II treated germ-free mice, showing increased cardiac fibrosis, macrophage and neutrophil accumulation, and increased cardiomyocyte area together with increased end-organ damage and angiotensin-II induced hypertension in the conventionally-raised controls [65], myocardial fibrosis was significantly enhanced in mice on a choline-rich or TMAO supplemented diet in the transverse aortic constriction model [113].…”
Section: Association Of the Gut Microbiota-derived Metabolite Trimethsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our observations in angiotensin-II treated germ-free mice, showing increased cardiac fibrosis, macrophage and neutrophil accumulation, and increased cardiomyocyte area together with increased end-organ damage and angiotensin-II induced hypertension in the conventionally-raised controls [65], myocardial fibrosis was significantly enhanced in mice on a choline-rich or TMAO supplemented diet in the transverse aortic constriction model [113].…”
Section: Association Of the Gut Microbiota-derived Metabolite Trimethsupporting
confidence: 89%
“…In addition to its role in promoting atherosclerotic lesion development, choline-rich diet or TMAO were demonstrated to exacerbate pressure overload-induced heart failure in mice that were subjected to a transverse aortic constriction [113]. Similar to our observations in angiotensin-II treated germ-free mice, showing increased cardiac fibrosis, macrophage and neutrophil accumulation, and increased cardiomyocyte area together with increased end-organ damage and angiotensin-II induced hypertension in the conventionally-raised controls [65], myocardial fibrosis was significantly enhanced in mice on a choline-rich or TMAO supplemented diet in the transverse aortic constriction model [113].…”
Section: Association Of the Gut Microbiota-derived Metabolite Trimethmentioning
confidence: 99%
“…63 In addition, elevation of TMAO level is a risk factor for development of HF in both diabetic and non-diabetic individuals. 64 In a murine LV pressure overload model, a diet enriched in TMAO or choline was shown to promote cardiac systolic dysfunction, together with severe cardiac fibrosis, 65 indicating a causative role of TMAO in promoting HF pathology. In addition, it is reported that TMAO contributes to progression of atherosclerotic plaque by reducing reverse cholesterol transport.…”
Section: Trimethylamine-n-oxidementioning
confidence: 99%
“…Several studies have found that elevated serum TMAO is associated with increased incidence of myocardial infarction, HF, and cardiovascular mortality [3540]. The mechanisms underlying these adverse associations between TMAO and cardiovascular have been partially described.…”
Section: Normal and Abnormal Gut Physiology: Implications For Patientmentioning
confidence: 99%